Full-Field Strain Characterizations and Fracture Process of Rock Blasting Using a Small-Scale Double-Hole Bench Model. (28th August 2020) - Yang, Jun; Liu, Xin; Xu, Zhenyang; Tang, Hongliang; Yu, Qi
Abstract : A small-scale double-hole bench model is designed with granite to study the fracture mechanism of rock blasting. By combining high-speed camera and digital image correlation, the full-field strain characterization and fracture process of the specimen bevel surface are investigated. The preliminary test results show that the strain concentration zone corresponds to the crack propagation location, and digital image correlation can well detect the crack propagation. In addition, through observing the crack propagation pattern on the specimen bevel surface, it can be seen that the fracture of the specimen is caused by the dominant horizontal crack and the dominant vertical crack, and the generation of the dominant horizontal crack takes precedence over that of the dominant vertical. Finally, the measurements of two-dimensional digital image correlation and three-dimensional digital image correlation are discussed.